Influence of tillage and mulching on growth, yield and economics of rainfed yellow sarson (Brassica rapa var glauca) in lateritic acid belt of West Bengal - MOITRA, R; GHOSH, D C; MAJUMDAR, S K; SARKAR, S (The Indian Journal of Agricultural Sciences, 2013)
A field experiment was conducted during the winter seasons of 1988-89 and 1989-90 to study the effect of tillage and mulching on yield and economics of yellow sarson [Brassica rapa (L.) Thell. emend. Metzger var glauca (Roxb.) Schulz., syn B. campestris L. ssp oleifera (Metzger) Sinsk, var yellow sarSon). The treatments comprising 3 tillage (2, 4 and 6 criss-cross ploughings) and 4 mulch levels (no mulch, soil-dust mulch, green mulch and dry-straw mulch) were laid out on a lateritic sandy-loam (Ultisol) soil. The tillage treatments did not show any significant influence on growth and yield of rainted yellow sarson, but application of mulch material particularly green coral creeper (Antigonon leplopus Hook. &. Am.) or dry straw greatly ineteased the growth and productivity of the crop. Two criss-cross ploughings at sowing with green or straw mulch @ 5 tonnes/ha at 15 days after sowing gave the highest yield (1.13 tonnes/ha) and benefit:cost ratio (1.4S). Soil-dust mulch also increased the yield of yellow sarSon compared with no mulch.